Surgical treatment of malignant paraganglioma with spinal invasion in a juvenile patient: A case report. Issue 39 (September 2019) - Liu, Shuzhong; Zhou, Xi; Song, An; Huo, Zhen; Li, William A.; Rastogi, Radhika; Wang, Yipeng; Liu, Yong
Abstract: Rationale: Paragangliomas are rare neuroendocrine tumors that originate in specialized cells derived from the neural crest with metastasis to the thoracic spine being among the rarest forms. Here, we are presenting a detailed analysis of a case of malignant paraganglioma in the thoracic spinal region in a 14-year-old boy. Our focus is to emphasize the importance of considering malignant paraganglioma as a diagnosis and guiding the perioperative management upon surgical treatment. The management of these unique cases has yet to be well-documented. Patient concerns: A 14-year-old boy presented with a 5-month history of continuous and progressive elevated blood pressure and back pain. The patient, who had been diagnosed of malignant paraganglioma in the left posterior mediastinum for 3 months, received surgical resection of paraganglioma in the left posterior mediastinum, which had involved the left intervertebral foramen of T4. However, the tumor was not completely resected during the first operation. Diagnoses: Magnetic resonance imaging of spine and positron emission tomography-computed tomography showed spinal cord compression secondary to the epidural component of the T4 mass, with increased marrow infiltration of the left T4 intervertebral foramen, which was difficult to be removed. Postoperative pathology confirmed the diagnosis of spinal involvement of malignant paraganglioma. Interventions: The patient underwent biopsy and percutaneous vertebroplasty of T4 and paravertebral lesions, and needle-track cement augmentation via a posterior approach. Outcomes: The patient's neurological deficits improved significantly after the surgery, and the postoperative period was uneventful at the 10-month follow-up visit. There were no other complications associated with the operation during the follow-up period. Lessons: Combined efforts of specialists from orthopedics, neurosurgery, thoracic surgery, and medical oncology led to the successful diagnosis and management of this patient. Malignant paraganglioma of thoracic spine, although rare, should be part of the differential diagnosis when the patient has a history of paraganglioma and presents with back pain and radiculopathy. We recommend the posterior approach for spinal decompression of the malignant paraganglioma when the tumor has caused neurological deficits. Osteoplasty by cement augmentation is also a good choice for surgical treatment. However, we need to take the potential risk of complications in bone cement applications into full consideration.